Integrating climate policies in the European environment: A policy report - Carlo Carraro; Alessandra Goria (Fondazione Eni Enrico Mattei (FEEM), 1999)
This report summarises the main ideas, proposals, scientific achievements, consensus and conflicting issues that emerged at the Second EFIEA Policy Workshop, held at Fondazione Eni Enrico Mattei, Palazzo delle Stelline, Corso Magenta 63, Milan, Italy, March 4th-6th, 1999. EFIEA, the European Forum for Integrated Environmental Assessment, is a concerted action funded by the Environment and Climate Programme of the European Commission, Directorate-General XII (contract no. ENV4-CT97-0450). The two main objectives of the EFIEA are: (i) to improve the scientific quality of integrated environmental assessment; (ii) to strengthen the interaction between environmental science and policy-making. In addition, the EFIEA fosters co-operation between scientists and decision makers inside the European Union, communication and co-operation outside the EU, and investigation of IEA techniques. The Second EFIEA Policy Workshop was devoted to improving communication and stimulating co-operation between different stakeholders, policymakers and scientists on the most relevant climate policy issues.
Keywords: D61; D63; F1; H2; H4; H5; O3; Q15; Q2; 330; Climate change; Government policies; Mitigation; Equity; Efficiency; Trading; Energy; Transports; Land-use; Klimaschutz; Umweltschutz; Wirkungsanalyse; Internationale Wirtschaftspolitik; Theorie; EU-Staaten